STRATEGI DEWAN KEMAKMURAN MASJID DALAM MEMBINA KELUARGA SAKINAH, MAWADDAH, WARAHMAH BAGI MUALAF DI KOTA MALANG (Studi Kasus Mualaf Center Masjid Agung Jami’ Kota Malang) - Muhammad Badrun Tamam Mageskar; Khoirul Asfiyak; Moh. Muslim (Jurnal Hikmatina, 2022)
The family is the smallest institution that has leaders and members, has responsibilities between individuals. Every human being desires a family full of love and compassion that is built without oppression without any dominating one party, according to what is commanded in Islam, namely the sakinah, mawaddah and warohmah families, how happy a family is filled with mutual love, affection, protection and mutual respect. . Families like this are formed by themselves and are not inherited from their ancestors, but thanks to the efforts of all members in the family who interact and communicate with each other in one household. To be able to carry out the functions, duties and responsibilities of each in the family with the provisions ordered by Allah SWT so that the whole family is able to live life in the world in accordance with the times. Based on initial observations, that the development of the sakinah mawaddah warahmah family, DKM Agung Jami' Malang City uses a strategy by taking a personal approach to the guidance participants, this is a special strategy used by DKM in fostering sakinah, mawaddah, and warahmah families. This personal approach was taken because the problems of the participants who took the guidance were different, such as those who were married and those who were about to get married. From the background of the research above, the researcher formulates the problem, namely how the strategy used by DKM Agung Jami' Malang City in fostering a sakinah, mawaddah, warahmah family for converts and what are the supporting and inhibiting factors of DKM Agung Jami' Malang City in fostering a sakinah, mawaddah family. , warahmah for converts. The purpose of this study is to describe the strategies used by DKM Agung Jami' Malang City in fostering sakinah, mawaddah, warahmah families for converts and to describe the supporting and inhibiting factors of DKM Agung Jami' Malang City strategies in fostering sakinah, mawaddah, warahmah families for converts. To achieve the above objectives, the research was carried out with the type of research being a case study, the approach used in this study was a qualitative approach. As for the data sources in this study, DKM, who is the head of the Mualaf Center management at the Great Mosque of Jami' Malang City, penghulu, extension workers, treasurer kua, kua staff, and the administration. The method used is observation, interviews and documentation, then the data processing and analysis techniques are carried out in three stages, namely data reduction, data presentation and conclusion drawing. The results showed several DKM strategies in fostering sakinah, mawaddah, warahmah families for converts, namely through lecture strategies, demonstration strategies, individual approaches, settlement discussions. The supporting factors of DKM in fostering include: facilities and infrastructure, readiness of DKM time in providing guidance, the existence of a translation book guide, the existence of self-motivation, the motivation of other colleagues, and the inhibiting factors are the absence of an official structure, the absence of a place to work. specifically in conducting coaching, lack of awareness from converts' families, work and distance traveled. Things that need to be considered as suggestions are the need to establish a center converting institution with an official structure so that the guidance converts can be more focused and maximized in receiving material, it is necessary to have a recruitment system through electronic media owned by the Jami' Great Mosque institution.Kata kunci: Strategi, Dewan Kemakmuran Masjid, Keluarga Sakinah Mawaddah Warahmah, Mualaf